(3ZGjI GdeCehd aj TQM RHOI GdCUhds - (3GdHZOGOj GdcGXej, GdLhGO GdHZOGOj, LhGO Hf SYO Hf LhGO, J (B1065(3g`s
(3ChdgG (B:s
...(3hQJHJg Ydi NeSI efGgL QJH GdCSJGP GdeUfa cJGHg gPG Ydi NeS efGgL(B...s
(3BNQgG (B:s
...(3hGdMGUd Cf GdeLJgO jYJHQ MGd bhI GdXf aj Pdc aeG cGf Cbhi aj Xfg jLH Ydjg GdYed Hg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B510s
(3GdPQjYI(B:(3L(B16(3,U(B61s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs